Sistem Informasi Berbasis Web untuk Layanan Ambulans di Puskesmas Tanggetada - Cencen; Rasyid, Rasmiati; Sumpala, Andi Tenri; Adawiyah, Rabiah (Journal Research on Computing Knowledge, 2024)
Ambulance services are an essential component of the healthcare system that necessitate rapid and effective administration. At Puskesmas Tanggetada, ambulance service management is conducted manually, frequently encountering issues such as inadequate coordination, delayed responses, and restricted public access to information. This study is to create and implement a web-based information system to facilitate the management of ambulance services at Puskesmas Tanggetada. The study technique encompasses requirements analysis, system design, system development utilizing web-based technologies, and functionality and user acceptance testing. The findings indicate that the built system includes essential functionality such as online ambulance service registration, real-time tracking of ambulance status, automatic user notifications, and the compilation of reports and statistics for service assessment. System testing demonstrates that these functionalities function as intended and can enhance service efficiency. Notwithstanding the system's beneficial effects, issues such as inadequate internet infrastructure and the community's digital literacy persist as significant problems necessitating smart remedies. This web-based information system provides an innovative technology solution and contributes significantly to the digitalization of local healthcare services